Overview on Karyotype Stasis in Atlantic Grunts (Eupercaria, Haemulidae) and the Evolutionary Extensions for Other Marine Fish Groups - Motta-Neto, Clóvis Coutinho da; Cioffi, Marcelo de Bello; Costa, Gideão Wagner Werneck Félix da; Amorim, Karlla Danielle Jorge; Bertollo, Luiz Antonio Carlos; Artoni, Roberto Ferreira; Molina, Wagner Franco (Frontiers in Marine Science, 2019)
Karyotype stasis, characterized by the absence of changes in chromosome number, genomic structure, and ploidy, is a recurrent condition in many biological groups, such as plants, amphibians, birds, and fishes. In fishes, the Percomorpha clade (>17,000 species), especially, its largest series, Eupercaria (>6,000 species and 161 families), shows an extensively shared karyotype with 2n=48 acrocentrics; the phylogenetic extension in this series is still unknown. Haemulidae (grunts) .a bounds the zoogeographic marine provinces of the Caribbean and Brazil, has a variable effect on the gene flow in diverse fish groups. Geographically, this barrier is located inside the distribution area of several fish species of Atlantic, allowing the examination of its role on the eventual karyotype differentiations in the populations of grunts. In this sense, cytogenomic analyses were carried out in eight haemulid species by conventional cytogenetic approaches (Giemsa staining, C-banding, and Ag-NORs technique), staining with base-specific fluorochromes, and two-color fluorescent in situ hybridization (FISH) with 5S and 18S rDNA probes. Additionally, we performed an exhaustive survey on the cytogenetic data of species from the Eupercaria series to assess the general context of karyotype divergences. Haemulid species and populations showed a pronounced sharing of karyotypes with 2n=48a, simple NORs, and reduced centromeric heterochromatin, apart from recurrent patterns of ribosomal 5S and 18S rDNA sites. Karyotype similarities persisted at intra- and congeneric levels in the Haemulidae family, indicating accentuated syntenic conservatism through large divergence periods. Stable karyotype patterns were extensively present in the majority of members from Eupercaria (88% of the clades in this series). These results indicate that karyotype stasis, which is found in a large spectrum of marine fishes, is a multifactorial process in terms of phylogenetic, biological, and biogeographic contexts.